Evaluating Outcomes of Selective Myectomy of Depressor Anguli Oris, Buccinator, and Platysma in Facial Synkinesis - Krippaehne, Elise; Valencia-Sanchez, Bastien A.; Bartho, Murray J.; Crawford, Kayva; Loyo, Myriam (Facial Plastic Surgery, 2025)
Selective myectomy has gained popularity for treating facial synkinesis.We examined the combined effectiveness of depressor anguli oris (DAO), partial buccinator, and platysma myectomies.Retrospective case series.Pre- and postoperative botulinum toxin-A (BTX-A) treatments of selective myectomy patients were collected. Facial photographs were analyzed using Emotrics + . Facial Asymmetry Index (FAI) and electronic facial paralysis assessment (eFACE) scores were calculated.Twenty patients underwent myectomies. Improvements (mean ± standard error) were seen in several smile metrics, including FAI by 2.80 ± 0.68 mm, nasolabial fold angle by 4.78 ± 1.83 degrees, and smile angle by 4.43 ± 1.18 degrees (all p < 0.05). Postoperative FAI was 2.79 mm. Total BTX-A decreased by 10.85 ± 4.48 units (p = 0.03). eFACE revealed improved oral commissure movement and platysmal synkinesis (p < 0.05 for both).Combined myectomies of the DAO, partial buccinator, and platysma clinically and statistically improve smile in facial synkinesis.
Keywords: selective myectomy; facial synkinesis; platysmectomy; facial asymmetry; botulinum toxin